Antimicrobial effect of propolis extract based on minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods. - Fatemehe Majdi (19825877) (2024)
Antimicrobial effect of propolis extract based on minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methods.